Online Purchasing Patterns And Intention To Purchase Through Internet : A Study On Malaysian Consumers' Perspective - Lim , Sin Lu (2009)
This study based on primary data collected from 300 sample respondents. The survey shows that more than half of the respondents have made online purchase before, and most of the experienced online purchasers are male, young, and highly educated.